2022
DOI: 10.1371/journal.pone.0270099
|View full text |Cite
|
Sign up to set email alerts
|

The effect of physical fatigue on the performance of soccer players: A systematic review

Abstract: This study aimed to carry out a systematic review to analyze, describe and discuss the effect of physical fatigue on the performance of soccer players. For this systematic review, searches were performed in Pubmed, Web of Science and SPORTDiscus electronic database until October 3, 2020, following the guidelines of PRISMA. A total of 12 articles met the inclusion criteria: i) healthy soccer players from any age group, competitive level or sex; ii) exposure to physical fatigue; iii) pre and post-physical fatigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…There is an extensive body of literature indicating fatigue may detrimentally impact subsequent physical activity and performance (Dambroz et al, 2022; Davidow et al, 2020; Head et al, 2016; Kempton et al, 2013; Knapick et al, 1991; Marcora et al, 2009). If physical risk perception is a cognitive mechanism to reduce potential self-harm (“this is risky, I may get hurt, so do not do it”) and fatigue is detrimental to physical skill, then one plausible mechanism to reduce harm likelihood would be for risk perception of physical activities to be influenced by fatigue states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an extensive body of literature indicating fatigue may detrimentally impact subsequent physical activity and performance (Dambroz et al, 2022; Davidow et al, 2020; Head et al, 2016; Kempton et al, 2013; Knapick et al, 1991; Marcora et al, 2009). If physical risk perception is a cognitive mechanism to reduce potential self-harm (“this is risky, I may get hurt, so do not do it”) and fatigue is detrimental to physical skill, then one plausible mechanism to reduce harm likelihood would be for risk perception of physical activities to be influenced by fatigue states.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between fatigue – both cognitive and physical – and subsequent physical task performance has been extensively studied (Dambroz et al, 2022; Davidow et al, 2020; Head et al, 2016; Kempton et al, 2013; Knapick et al, 1991; Marcora et al, 2009; Smith et al, 2015). As early as 1891, Mosso (1904) wrote about fatigue affecting his later physical performance.…”
mentioning
confidence: 99%
“…Our study implemented SSGs in continuous and fractional regimens, without finding significant differences in technical performance or perceived enjoyment during the game. Previously, systematic reviews have reported a relationship between physical fatigue and technical performance [ 28 ]; therefore, it might be concluded that regimens that generate a higher workload could negatively affect performance. Studies that have compared the two types of regimens have found that fractional SSGs generate a greater internal and external load [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…As physical performance is an important component of soccer match performance ( Julian, Page, & Harper, 2020 ; Forcher et al, 2022b ; Dambroz, Clemente, & Teoldo, 2022 ; Sarmento et al, 2022 ), the aim is to optimize these capabilities. In order to individually tailor training programs maximizing positive physiological adaptation and at the same time preventing injury and illness, careful load monitoring is required ( Halson, 2014 ; Akenhead & Nassis, 2016 ; Bourdon et al, 2017 ; Impellizzeri et al, 2019 ; Miguel et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%